Novel compatibilizers and plasticizers developed from epoxidized and maleinized chia oil in composites based on PLA and chia seed flour. (15th June 2022) - Dominguez-Candela, Ivan; Gomez-Caturla, Jaume; Cardona, S.C.; Lora-García, Jaime; Fombuena, Vicent
Graphical abstract: Highlight: Novel composites of polylactide acid (PLA) based on chia seed flour (CSF) have been manufactured to contribute to circular economy. Epoxidized and maleinized chia seed oil have been employed as environmentally friend plasticizer/compatibilizer. The ductile properties are highly improved in composites with epoxidized and maleinized chia seed oil due to its plasticizing effect. The interfacial adhesion between CSF filler and PLA matrix is enhanced using all compatibilizers. Compatibilized PLA/CSF composites are fully disintegrated under compost conditions. Abstract: Novel compatibilizers and plasticizers derived from epoxidized chia seed oil (ECO) and maleinized chia seed oil (MCO) have been applied in composites based on poly(lactic acid) (PLA) and 15 wt% chia seed flour (CSF). Results obtained have been compared to conventional silane coupling agent, (3-glycidyloxypropyl) trimethoxysilane (GPS), and a petroleum-based compatibilizer, poly(styrene-co-glycidyl methacrylate) copolymer (Xibond, ®). The compatibilization effect of green composites were assessed by FTIR. The addition of all four compatibilizers improved the ductile mechanical and thermal properties of the composites. The morphology analysis revealed an improvement of interfacial adhesion of the CSF particles into the PLA matrix. In particular, ECO and MCO composites showed a roughness with long filaments in their morphology which plays a crucial role in improving the ductile properties highly. The elongation at break was 10 and 8 times higher using ECO and MCO, respectively, compared to uncompatibilized composite. Moreover, the composites manufactured showed low values (<9%) in the water uptake assay and a negligible compostability delay. The use of novel compatibilizers based on modified vegetable oils could mean an interesting proposal to obtain an entirely environmentally friendly composite with a remarkable ductile property.